The Development of Physics E-Module Based on Discovery Learning on Optics Materials in Senior High Schools - Ghadzia, Ghadzia; Husna, Husna; Yanti, Iing Rika (Jurnal Pendidikan Fisika, 2023)
This study aims to develop a physics e-module based on discovery learning that is valid, practical, and effective for high school students. The type of research used was research and development (R&D) with 4-D model research procedures, namely define, design, develop, and disseminate. The participants in this study were 36 students of class XI IPA 1 SMAN 12 Padang. In this study, the initial analysis of the questionnaire was carried out. The data obtained were then analyzed to determine the validity, practicality, and effectiveness of the e-module developed. To assess the validity of the module, two material experts and one media expert were involved, while to find out the practicality level, 36 students and one physics teacher were given their evaluation. Furthermore, the effectiveness of the module was assessed using the N-Gain calculation. The results show that the validation score was 85.46% (very valid category), while the practicality test scored 94.11 percent (very practical category). Meanwhile, the effect of the physics e-module is also quite significant, with the results of the t-test 20.02 >1.68957 and the N-gain calculation producing a score of 0.71. These indicate that the physics e-modules based on discovery learning that has been developed are categorized as very valid, very practical, and effective. Therefore, the use of the discovery learning-based physics e-module is appropriate to improve students' conceptual understanding.